2021
DOI: 10.3390/ijms22020583
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Airway Secretions: New Insights in Lung Diseases

Abstract: Lung diseases (LD) are one of the most common causes of death worldwide. Although it is known that chronic airway inflammation and excessive tissue repair are processes associated with LD such as asthma, chronic obstructive pulmonary disease (COPD) or idiopathic pulmonary fibrosis (IPF), their specific pathways remain unclear. Extracellular vesicles (EVs) are heterogeneous nanoscale membrane vesicles with an important role in cell-to-cell communication. EVs are present in general biofluids as plasma or urine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 177 publications
0
24
0
Order By: Relevance
“…According to the results of the NanoFCM particle characterization, EV populations isolated from the apical cell side were mainly composed of vesicles with diameters matching the size range of the exosomes. Contrarily, on the basolateral cell side, median vesicle diameters were noticeably larger, consistent rather with the size of the microvesicles than with the exosomes [37,38]. FACS analysis for exosomal marker proteins revealed the presence of exosomes in both apical and basolateral samples, although apical EVs seemed to express exosomal marker proteins to a greater extent than the basolateral vesicles.…”
Section: Discussionmentioning
confidence: 70%
“…According to the results of the NanoFCM particle characterization, EV populations isolated from the apical cell side were mainly composed of vesicles with diameters matching the size range of the exosomes. Contrarily, on the basolateral cell side, median vesicle diameters were noticeably larger, consistent rather with the size of the microvesicles than with the exosomes [37,38]. FACS analysis for exosomal marker proteins revealed the presence of exosomes in both apical and basolateral samples, although apical EVs seemed to express exosomal marker proteins to a greater extent than the basolateral vesicles.…”
Section: Discussionmentioning
confidence: 70%
“…Besides, the membrane composition of EVs is highly dynamic, heterogeneous and dependent on the cellular source and environmental conditions [ 50 ]. EVs are released by almost all cell types such as platelets, tumor cells, dendritic cells, T and B lymphocytes, eosinophils, epithelial cells, endothelial cells, and mesenchymal stem cells (MSCs) [ 51 ]. Currently, some databases on EV composition as EVpedia, Exocarta and Vesiclepedia [ 52 , 53 , 54 ] include the most recent information about their composition.…”
Section: Exosomesmentioning
confidence: 99%
“…Although BALF analysis is the most commonly used technique for the assessment IPF, induced sputum has been regarded as a safer and less invasive method and has been shown to be clinically valuable for respiratory diseases ( 110 , 111 ). Previous research has demonstrated that the expression and production of proteins, such as insulin-like growth factor binding protein 2, IL-8 and MMP-7 in the sputum of patients with IPF is significantly increased, which may be related to the disease ( 112 ).…”
Section: Role Of Exosomal Micrornas In Pulmonary Fibrosismentioning
confidence: 99%